EFFECT THE PROBLEM-BASED LEARNING MODEL ON ABILITY MULTIPLE REPRESENTATIONS OF XI-GRADE STUDENTS ON ACID-BASED TOPIC - Datul, Ifa; Ardhana, Ivan Ashif (Universitas Negeri Surabaya, 2024)
It takes the ability to conceive at three different levels of representation, macroscopic, sub microscopic, and symbolic to comprehend acid-base material. Still, most students are unable to make the connection between the three levels of representation. As a result, instruction that helps students connect various representations in acid-base content is required. The PBL model is one appropriate learning paradigm that can be used. The purpose of this study is to determine whether PBL models and conventional models differ in their capacity to support numerous representations. A quantitative experiment using a quasi-experimental study design is the research methodology employed. A post-test-only control group design is used in this study. The samples of this study were XI MIPA 3 as a control group of 34 students and XI MIPA 4 as an experimental group of 33 students. Simple random sampling was used to get the research samples. A post-test consisting of multiple-choice questions was the instrument utilized. With a reliability score of 0,802 across 20 items, the empirical validation results indicate that all instruments are appropriate for use as research measures. methods for gathering data through tests. Data collection techniques in the form of tests. The data analysis technique in this study is descriptive and inferential statistics with hypothesis testing in the form of the Independent Sample t-Test. With a sig value of 0,000 < 0,05, the results demonstrated that there is a difference in the ability of multiple representations between those taught using the PBL model and those taught using the conventional model.